Trade Performance and Specialization Dynamics of the Five Most Traded Products between Bangladesh and the Rest of the SAARC Countries - Sumi, Asma Akter; Hossain, Md. Monzur; Islam, Md. Sohanul; Acharjee, Partha; Hossain, Md Shafiul; Bairagi, Mithun (International Journal of Economics and Financial Issues, 2025)
This study focuses on the trade specialization of significant products in Bangladesh’s trade basket from 2008 to 2021 in forming SAFTA under SAARC (South Asian Association for Regional Cooperation). The study utilized the Lafay Index to identify trade specialization; the prime products of Bangladesh are determined based on the continuous presence of any specific product within the list of top 10 products of Bangladesh each year during the study period. The study concluded that four of the five significant products are from the Garments sector, and the remaining one is from the Vegetable Oil sector. The significant products identified exhibited a relatively high degree of trade specialization in the context of SAARC and faced stiff competition from its neighbouring country, India. The post hoc Games-Howell test also revealed that most of the differences are statistically significant for all the major products. Based on the findings, this paper also offered the policy prescription for SAFTA. This research looks at the dynamics of specialisation and trade performance in Bangladesh in comparison to other SAARC countries. It helps shed light on the trading dynamics inside one of the most populous and economically varied areas of the world by centring on the local setting.